Profil Des Infections Ostéoarticulaires En Consultation Rhumatologique Au CHU- Kara (Togo) - Houzou, Prénam; Kakpovi, Kodjo; Fianyo, Eyram; Koffi-Tessio, Viwalé Etonam S.; Tagbor, Komi Cyrille; Landoh, Dadja Essoya; Oniankitan, Owonayo; Mijiyawa, Moustafa (European Scientific Journal, ESJ, 2017)
Introduction: Osteoarticular infections remain public health problems in Africa. We aim at determining the clinical forms, topographic and etiological osteoarticular infections in a rheumatology unit of northern Togo. Methods: We conducted a cross-sectional study from April 2012 to March 2015 on inpatient records having suffered from musculoskeletal infection. Results: Of the 1813 patients admitted to the department in three years, 86 (4.74%) suffered from musculoskeletal infection. Of them, 36 (41.86%) were men and 50 (58.1% 4) were women, with a sex ratio (M/F) of 0.72. The mean age of the patients was 45 years. The mean duration of disease progression was 3.5 months. The different clinical forms observed were: spondylitis (47 patients, 54.65%), infectious arthritis (31 cases, 36.05%) and osteomyelitis (eight cases; 9.30%). The infection was likely tuberculous in 53 patients (61.63%), including 44 cases of Pott's disease. A banal germ was mentioned in the 33 others patients (38.37%). In four cases, the germ was isolated: Staphylococcus aureus (three cases) and Staphylococcus epidermidis (one case). The joints most affected by the infection were the hip (nine patients) and the knee (eight patients). Infection was multifocal in 14 cases (16.27%). The main risk factors for the infection identified were: promiscuity and poor hygiene (59.30%), alcoholism (26.74%) and retroviral infection (12.79%). Conclusion: This study and joint infections are a common reason for rheumatology consultation in northern Togo with a significant share of multifocal forms.